2003
DOI: 10.1016/s0399-1784(02)01229-x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, persistence and change in the macrobenthos of the lagoon of Lesina (Apulia, southern Adriatic Sea)

Abstract: The benthic community of the lagoon of Lesina was studied from July 2000 to June 2001. The distribution of the main macrophytobenthic species was recorded by visual census at 24 stations in July 2000. The macrofauna, from both hard and soft substrates, was analyzed at five stations with seasonal frequency; in addition, the main hydrologic parameters were recorded monthly. The lagoon was mainly characterized by brackish water, with salinity values decreasing from west to east (annual mean: 23.3 psu). It showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…4). These results are consistent with those obtained by Marzano et al (2003) for Lesina lagoon and, similarly, many studies have shown a marked influence of organic enrichment on quali-quantitative composition of macrobenthos community (Gravina et al 1989;Labrune et al 2007;Mucha and Costa 1999;Sardà et al 1995;Sordino et al 1989).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…4). These results are consistent with those obtained by Marzano et al (2003) for Lesina lagoon and, similarly, many studies have shown a marked influence of organic enrichment on quali-quantitative composition of macrobenthos community (Gravina et al 1989;Labrune et al 2007;Mucha and Costa 1999;Sardà et al 1995;Sordino et al 1989).…”
Section: Discussionsupporting
confidence: 91%
“…On the basis of these observations (highlighted by PCA analysis also), a not marked but evident difference between the two lagoons was observed and supported by ANOSIM test that suggested a greater influence of external sources on sediment macronutrient distributions in Varano rather than in Lesina lagoon. In particular, these results indicate that the primary sources of organic matter in the sediments of Lesina lagoon (particularly in the western area) could be related to a high primary production (phanerogams) (Cozzolino 1995;Marzano et al 2003) rather than a loading of high amounts of urban waste waters, as highlighted by ordination diagrams (Fig. 3, no influence of external water input).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The average water depth is 0.8 m, with the maximum of less than 2 m (Ricci Lucchi et al 2006). Bottom sediments mainly consist of mud and sand (Nonnis Marzano et al 2003). Like the lagoon of Orbetello, the lagoon of Lesina has experienced a progressive eutrophication followed by occasional dystrophic crises due to the abnormal proliferation of the green algae Valonia utricularis (Manini et al 2003).…”
Section: Lagoon Of Lesinamentioning
confidence: 99%
“…Zoostera noltii and Ruppia cirrhosa are the most abundant macrophytobentos species in the western and central-eastern basin respectively. Macrozoobenthos mainly consists of mussels, anellida and crustaceans (Nonnis-Marzano et al 2003).…”
Section: Study Areamentioning
confidence: 99%